(untitled) (Journal of Asian Development Studies, 2025)
The objective of this study is to investigate the relationship between expressive suppression and job performance among employees in textile mills in Pakistan. It aims to fill this gap and provide practical implications for workers; many of whom work long shifts from morning until evening or night and frequently suppress their emotions. A cross-sectional correlational research design with purposive sampling is employed to collect data from workers across various departments of textile mills in Pakistan. The minimum age criterion is 18 years, and both male and female employees who have been working in the textile mill for at least one year are included. Two scales are used: the Expressive Suppression subscale of the Emotion Regulation Questionnaire and the short version of the Self-Assessment Scale of Job Performance. Findings revealed a significant negative relationship between expressive suppression and job performance, and regression analysis further indicated that expressive suppression significantly and negatively predicts job performance among textile mill employees in Pakistan. The study offers comprehensive implications, including the need for legal and legislative reforms, the involvement of mental health professionals in raising awareness among managers and owners, encouragement for labour departments to implement effective measures, and support for employees in seeking mental health assistance.